Publication Ethics: Awareness & Knowledge among Medical Faculties - Ashutosh Baliram Potdar; Vinay Manjunath Raj; Pratap Singh Rathod; Pallavi Ashutosh Potdar (Indian Journal of Forensic Medicine & Toxicology, 2021)
Publication ethics is related with ethical aspects of publication of scientific data to ensure high qualityscientific publication in the current era of evidence-based medicine. Violation of publication ethics alsoknown as scientific misconduct may be committed by researchers knowingly and unknowingly due to variousreasons. Present study inducted 130 medical faculties from a medical college providing self-administeredquestionnaire regarding awareness about publication ethics using Google forms. Among those 94 facultiesresponded and 75% of the faculties were in favor of gift authorship and did not perceive it as a misconduct.83% of the faculties were aware that violation of publication ethics would affect career of all the involvedauthors. Almost 56% believed that falsification or fabrication of data is acceptable and 58% faculties felt itacceptable to split the results of a study and publish it separately. Considering the lack of awareness amongmedical faculties scientific misconduct, it is recommended that a formal educational session of publicationethics is necessary